Friendships and Search Behavior in Labor Markets - Sterling, Adina D. (Management Science, 2014)
This paper examines how organizations use employee networks to contend with job seekers' search behavior. According to prior research, in markets where job seekers engage in nonsequential job search, organizations respond with tactics such as exploding offers and recruiting candidates earlier. In this paper, I posit that organizations have a social structural response. I argue that in an attempt to avoid problems related to candidates' job search, organizations are more likely to provide job offers to candidates with friends in the hiring organization than to those without friends. I test and find support for this hypothesis in a study of entry-level professionals in business and law. After a period of trial employment, candidates were more likely to receive job offers from organizations if they had a friend employed there than if they did not. The implications of this study for research on labor markets, networks, and inequality are discussed. This paper was accepted by Jesper Sørensen, organizations.